2018
DOI: 10.1188/18.cjon.e18-e22
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Therapy: Evaluation of the Safety of Performing Core Needle Biopsy of the Breast Without Suspending Medication

Abstract: None of the 42 women who completed core needle biopsy of the breast while on antithrombotic therapy reported postdischarge bleeding, and 2 reported hematoma, supporting the safety of continuing antithrombotic therapy in patients who undergo core needle biopsy of the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this latter study, the authors defined hematomata as clinically significant if they caused significant post-procedure discomfort or required clinical follow-up, surgical or percutaneous drainage, or hospital admission. A recent study by Cameron et al [21] from 2018 (with only n = 42 patients) found no post-discharge bleeding after CNB in patients who were on anti-thrombotic therapy. All these above-mentioned studies display high variability in their design (including follow-up), in the investigated medication regimens, and in the biopsy methods used (modality and gauges), which impedes comparing or generalizing their results [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this latter study, the authors defined hematomata as clinically significant if they caused significant post-procedure discomfort or required clinical follow-up, surgical or percutaneous drainage, or hospital admission. A recent study by Cameron et al [21] from 2018 (with only n = 42 patients) found no post-discharge bleeding after CNB in patients who were on anti-thrombotic therapy. All these above-mentioned studies display high variability in their design (including follow-up), in the investigated medication regimens, and in the biopsy methods used (modality and gauges), which impedes comparing or generalizing their results [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, extrapolation of these results to patients on anticoagulants or multiple agents is cautioned. Another more recent study of 42 patients on various anticoagulants (including 5 on a direct oral anticoagulant [DOAC]) undergoing breast core biopsy, a 4% rate of self‐reported hematoma (classified as not clinically significant) was reported when anticoagulants were continued 13 …”
Section: Management Of Antithrombotic Agentsmentioning
confidence: 99%